Reticular Outflow, Rumen Dynamics, and Ingestive Behavior in Buffaloes (Bubalus bubalis) Fed Diets with Different Sources of Energy - dos Santos Soares, Franklin Delano; Pinto de Carvalho, Gleidson Giordano; Vieira Pires, Aureliano José; Santos Pina, Douglas dos; Gomes de Azevêdo, José Augusto; Leite, Laudi Cunha; Borja, Maikal Souza; Silva Magalhães, Tamires da; Melo Lopes de Araújo, Maria Leonor Garcia; Santos Brant, Lara Maria; de Freitas Júnior, José Esler (Journal of Buffalo Science, 2025)
The objective of this study was to evaluate the effects of two energy sources, associated or not (crude glycerin and castor oil) in buffaloes' diets on intake, digestibility, rumen kinetics, feeding behavior, nitrogen balance, microbial protein synthesis, rumen fermentation, and blood metabolites. Four ruminally-cannulated Murrah buffaloes [526 ± 29 kg of initial BW] were randomly assigned according to a 4 x 4 Latin square design in which the animals were randomly allocated to each treatment: CONT = control with soybean meal associated with ground corn; GLY = crude glycerin, dietary inclusion of 90 g/kg; CAO = castor oil, dietary inclusion of 50 g/kg; GLYCAO = crude glycerin associated with castor oil, dietary inclusions of 50 g/kg GLY and 50 g/kg CAO. A higher ruminal renewal rate of DM and NDF and DM passage rate was observed for animals fed CON and GLY than the other diets (P < 0.05), the same fact was observed for rumination efficiency grams DM/hour (P < 0.001). Among the feed sources, crude glycerin can partially replace ground corn in the buffalo’s diet without compromising intake, nutrient metabolism, and rumen dynamics.